PEMBUATAN PUPUK ORGANIK CAIR (POC) DARI LIMBAH KOTORAN TERNAK BABI DI DESA LA’USO KECAMATAN ONOHAZUMBA - Berkat Yakin Kasih Lase; Nerdiana Loi; Safri Idayani Lombu; Dayanti Putri D. Waruwu; Ferdin Buulolo; Lisman Berkat Gulo; Memori Syukur Rahmat Zai; Novelix Halawa; Riwaldin Lugu; Wilan Perisai Ndruru (Universitas Nias Raya, 2025)
Liquid Organic Fertilizer (LOF) derived from pig manure waste presents an environmentally friendly and efficient solution for improving soil fertility and agricultural productivity. Traditional pig farming activities generate waste that is rich in nutrients such as nitrogen (N), phosphorus (P), and potassium (K), but it is often underutilized, leading to environmental pollution. This study aims to design and test a method for producing LOF using pig manure as the primary material, involving both aerobic and anaerobic fermentation, the addition of decomposer microorganisms, and the formulation of solid sediments for stabilization. The fermentation process takes approximately 21–30 days. Evaluation parameters include pH, organic carbon (C) content, N, P, K levels, effective microbial population, and application effectiveness on vegetable crops in a field trial. The results showed that the LOF met quality standards—neutral pH (6.5–7), sufficient macronutrient content (N 1.2%, P 0.8%, K 1.5%), and a high population of active microbes. Application of LOF (5 mL/L once a week) to mustard greens and water spinach improved plant growth (height, leaf count) and productivity by approximately 20–30% compared to the control. In addition to being efficient, this method positively impacts the environment by reducing odor, gas emissions, and pollution potential. This locally made product also holds economic potential for small-scale farmers and agricultural communities. This work program was carried out by students from KKN Group 20 in La’uso Village as part of the development of Liquid Organic Fertilizer (LOF). We implemented the program according to the proposal submitted and with permission from the La’uso village government. The implementation prioritized communication and interaction with village officials and the community. The success of this KKN program was made possible by the strong support from the people of La’uso Village, Onohazumba District.